2015
DOI: 10.1111/medu.12571
|View full text |Cite
|
Sign up to set email alerts
|

A review of teaching skills development programmes for medical students

Abstract: Although several types of programmes have been shown to subjectively improve the teaching skills of undergraduate medical students, characterisation of the objective outcomes of these initiatives is lacking and requires further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
74
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 43 publications
(263 reference statements)
4
74
0
Order By: Relevance
“…Though more rigorous quality assurance would be necessary if the sessions form part of the school's formal curriculum. A recent review identified peer teaching programmes, teaching workshops and community outreach programmes as the three leading initiatives for developing students' teaching skills (Marton, et al, 2015). Peer observation of peer teaching may also be valuable for ongoing development of teaching skills (Rees, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Though more rigorous quality assurance would be necessary if the sessions form part of the school's formal curriculum. A recent review identified peer teaching programmes, teaching workshops and community outreach programmes as the three leading initiatives for developing students' teaching skills (Marton, et al, 2015). Peer observation of peer teaching may also be valuable for ongoing development of teaching skills (Rees, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A small but increasing number of medical schools, however, have now begun to offer teacher training to medical students, mostly as electives, incidentally as a mandatory course [46] and some schools offer longer elective teacher training pathways [7]. Training teaching skills requires practice opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…Given the recent rise in popularity of peer teaching [4], and the mandate for students to develop teaching skills [2, 3], a number of teaching skills development programmes have been created for medical students [5]. Such programmes, aimed at improving the quality of teaching provided by students, have been classified broadly into three approaches: learning through experience of peer teaching, teacher training workshops, and students teaching school pupils in outreach events [5].…”
Section: Introductionmentioning
confidence: 99%
“…Such programmes, aimed at improving the quality of teaching provided by students, have been classified broadly into three approaches: learning through experience of peer teaching, teacher training workshops, and students teaching school pupils in outreach events [5]. Another method for improving the quality of teaching, which builds on learning from experience through peer teaching, is Peer Observation of Teaching (POT).…”
Section: Introductionmentioning
confidence: 99%